Unusually Aggressive Actinic Keratosis of the Eyelid and Conjunctiva - Jana Al-Hage; Julien Masliah-Planchon; Pierre Sohier; Livia Lumbroso-Rouic; Ivan Bieche; Selim Aractingi (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)